Analisis kebutuhan: bumper videos interaktif etnografis dengan pendekatan gamifikasi di sekolah dasar - Dewinta Aulia Savitri; Aswasulasikin Aswasulasikin; Makmum Raharjo (Jurnal Konseling dan Pendidikan, 2025)
This study aims to analyze the needs for developing ethnographic bumper videos based on gamification in Natural and Social Science (IPAS) learning at the elementary school level. A descriptive qualitative approach was employed involving 12 teachers and 324 students from three elementary schools in Palembang. The instrument was constructed based on six main aspects pedagogical, technical, cognitive, aesthetic, socio-cultural, and evaluative integrated across four components: students, teachers, media, and instructional design. Data were collected through observation, semi-structured interviews, and questionnaires, then analyzed using percentage techniques and Spearman’s rank correlation. The findings revealed that all aspects were in the high to very high category, with strong positive correlations (rs = 0.67–0.78) between school-based learning needs and home learning activities. Cognitive and aesthetic aspects emerged as the dominant needs, emphasizing the importance of visually engaging designs that enhance information processing efficiency. These results affirm that multidimensional needs analysis is essential for developing digital learning media that are contextual, adaptive, and aligned with the Merdeka Curriculum, contributing to effective and culturally relevant learning experiences.